Caught in the Feed: How Social Media and Lifestyle Override Financial Awareness Among Students - Hayatie, Marliza Noor; Dewi, Nurul Afianingrum Rahma; Nadiar, Rahmi; Izzadieny, Fitra (Quantitative Economics and Management Studies, 2025)
This study investigates the influence of social media, lifestyle, and personal financial management on students’ consumptive behavior. The research was conducted at Tanah Laut State Polytechnic involving students of the Accounting Study Program from the 2022 and 2023 cohorts. A total of 181 respondents were selected using purposive sampling. The study adopted a quantitative approach with data collected through a structured questionnaire. The collected data were analyzed using multiple linear regression assisted by SPSS version 26. The results reveal that, partially, social media and lifestyle have a significant and positive influence on students’ consumptive behavior. In contrast, personal financial management does not significantly affect students’ consumptive tendencies. The simultaneous analysis indicates that all three variables social media, lifestyle, and personal financial management collectively have a significant positive influence on consumptive behavior among students. The findings of this study suggest that digital exposure and lifestyle orientation are dominant factors influencing consumption decisions among students, whereas internal financial control has a weaker individual impact. These results provide a clear overview of the behavioral tendencies in student consumption and highlight the role of social and financial factors in shaping those behaviors.